On the Nanomechanical and Viscoelastic Properties of Coatings Made of Recombinant Sea Star Adhesive Proteins - Lefevre, Mathilde; Tran, Thi Quynh; De Muijlder, Thomas; Pittenger, Bede; Flammang, Patrick; Hennebert, Elise; Leclère, Philippe (Frontiers in Mechanical Engineering, 2021)
To attach to surfaces in the sea, sea stars produce proteinaceous adhesive secretions. Sfp1 is a major constituent of this adhesive, where it is present in the form of four subunits (named Sfp1α to δ) displaying specific protein-, carbohydrate- and metal-binding domains. Recently, two recombinant proteins inspired from Sfp1 have been produced: one corresponding to the C-terminal part of Sfp1β and the other to the full-length Sfp1δ. Adsorption ability tests showed that both recombinant proteins were able to adsorb and to form coatings on different surfaces in artificial seawater as well as in Tris buffer supplemented with NaCl or CaCl2. In this study, we used Atomic Force Microscopy (AFM) to characterize the nanomechanical properties of these coatings with an emphasis on functional characteristics such as adhesive properties and modulus of elasticity. We used AFM techniques which are the most appropriate to characterize the coating microstructure combined with the mapping of its nanomechanical properties.